Discovery of Benzopyrrolizidines as Promising Antigiardiasic Agents - Auriostigue-Bautista, Juan Carlos; Hernández-Vázquez, Eduardo; González-Calderón, David; Figueroa-Romero, Jorge Luís; Castillo-Villanueva, Adriana; Torres-Arroyo, Angélica; Ponce-Macotela, Martha; Rufino-González, Yadira; Martínez-Gordillo, Mario; Miranda, Luis D.; Oria-Hernández, Jesús; Reyes-Vivas, Horacio (Frontiers in Cellular and Infection Microbiology, 2022)
Current treatments for giardiasis include drugs with undesirable side effects, which increase the levels of therapeutic desertion and promote drug resistance in the parasites. Herein, we describe the antigiardiasic evaluation on Giardia lamblia trophozoites of a structurally diverse collection of 74 molecules. Among these scaffolds, we discovered a benzopyrrolizidine derivative with higher antigiardiasic activity (IC50 = 11 µM) and lower cytotoxicity in human cell cultures (IC50 = 130 µM) than those displayed by the current gold-standard drugs (metronidazole and tinidazole). Furthermore, this compound produced morphologic modifications of trophozoites, with occasional loss of one of the nuclei, among other changes not observed with standard giardicidal drugs, suggesting that it might act through a novel mechanism of action.